Changing the Rotterdam-Rijnmond regional fire service: A multi-dimensional approach for analysing strategies of change. Issue 2 (10th December 2019) - Koppenjan, Joop; van Sluis, Arie; van der Meer, Frans-Bauke; Kuipers, Ben; van Paridon, Kees
Abstract : Purpose: The purpose of this paper is to identify critical success factors for the management of complex change processes in fire service organizations and to apply these in a case study of the Rotterdam-Rijnmond fire service. Design/methodology/approach: The paper provides review of literature on organizational change, case study of the Rotterdam-Rijnmond fire service supported by the analysis of policy documents and 30 semi-structured interviews with key persons. Findings: Combining different theoretical approaches helps to get a more complete picture of important issues and dilemma's in the management of change processes – which is a first step in the successful implementation of changes – whereas other approaches tend to emphasize only some and overlook others. Applied in a case study, this approach revealed serious weaknesses in the management of change within the Rotterdam-Rijnmond fire service and offered practical guides for solutions. Originality/value: This paper combines insights from different theoretical approaches into a more integrated perspective that aims to be helpful as a practical tool for designing and implementing complex changes in fire service organizations.